2014
DOI: 10.3892/br.2014.304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural flavonoids, stilbenes and caffeic acid oligomers on protein glycation

Abstract: Abstract. The aim of the present study was to identify the inhibitory activity of natural flavonoids, stilbenes and caffeic acid oligomers on protein glycation. Antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl radical-scavenging activity. The production of 3-deoxyglucosone (3-DG) and advanced glycation end products (AGEs) by glycation reactions were determined by high-performance liquid chromatography and fluorescence, respectively. Certain flavonoids, stilbenes and caffeic acid oligomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
(22 reference statements)
2
12
0
Order By: Relevance
“…The Trolox equivalent antioxidant capacity was 0.60 μmol Trolox/mg (Figure c). The antioxidant property of stilbenes observed in our study corresponded with that observed in previous studies (Reinisalo et al, ; Sasaki et al, ). In addition, the antioxidant property of stilbenes can function against advanced glycation end products by glycation reactions (Sasaki et al, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The Trolox equivalent antioxidant capacity was 0.60 μmol Trolox/mg (Figure c). The antioxidant property of stilbenes observed in our study corresponded with that observed in previous studies (Reinisalo et al, ; Sasaki et al, ). In addition, the antioxidant property of stilbenes can function against advanced glycation end products by glycation reactions (Sasaki et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The antioxidant property of stilbenes observed in our study corresponded with that observed in previous studies (Reinisalo et al, ; Sasaki et al, ). In addition, the antioxidant property of stilbenes can function against advanced glycation end products by glycation reactions (Sasaki et al, ). Moreover, it can function against oxidative stress and aging‐related diseases (Reinisalo et al, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…CA exerted antioxidant and anti‐inflammatory effects by scavenging DPPH free radicals and down‐regulating inflammatory mediators such as COX‐2, iNOS and NF‐ κ B. Previous studies have reported the effects of caffeic acid oligomers on protein glycation, but the mechanisms of CA inhibiting glycation are less …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the effects of caffeic acid oligomers on protein glycation, but the mechanisms of CA inhibiting glycation are less. [14] The Glu-BSA (Bovine Serum Albumin) system is a common model for studying AGEs by the reaction of the carbonyl group of glucose with the free amino group of the protein. Previous studies have shown that free radicals are involved in the formation of AGEs.…”
Section: Introductionmentioning
confidence: 99%